Biochemical Markers as Predictor of Preterm Labor - and Their Clinical Relevance - the Current Status - Suneeta Singh; Madhusudhan Dey; Sanjay Singh; Shibu Sasidharan (Gynecology Obstetrics & Reproductive Medicine)
Preterm birth is associated with significant perinatal morbidity and mortality. Spontaneous preterm birth accounts for upto 75% of all preterm births. A number of maternal and fetal characteristics have been associated with preterm birth. With better understanding of the pathophysiology of preterm birth, various biochemical markers have been studied extensively to predict the preterm birth efficiently so as to intervene appropriately and timely in the cases that would benefit from treatment. This paper provides a summary of the current literature on the use of biochemical markers in predicting spontaneous preterm birth in symptomatic and high risk-asymptomatic women. Evidence from the literature suggests cervico vaginal fetal fibronectin,interleukin-6, phosphorylated Insulin-like growth factor binding protein-1(phIGFBP1), placental alpha macroglobulin-1 (PAMG-1) and serum